2016
DOI: 10.1016/j.dib.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Data on clinical significance of second trimester inflammatory biomarkers in the amniotic fluid in predicting preterm delivery

Abstract: In this article second trimester amniotic fluid biomarkers are measured for correlation with preterm delivery. One additional milliliter of amniotic fluid is collected during amniocentesis for dosages of IL-6, MMP-9, CRP and glucose levels, along with maternal serum CRP and glucose. MMP-9 and Il-6 levels were measured with the corresponding Human QuantikineR ELISA Kit (R&D systems) according to the instructions provided by the manufacturer. Cut-off values for AF MMP-9 and IL-6 were fixed by the kit sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The results of previous studies are conflicting, most likely due to dissimilarities in study design and diversities in study populations [26]. Some of the previous studies have reported higher levels of inflammatory biomarkers in mid-trimester amniotic fluid in women with a subsequent spontaneous PTD [21,23,37,[40][41][42][43][47][48][49][50]53,54,58], whereas other studies did not find any significant differences [25,26,38,39,[44][45][46]51,52,55,59]. Our study design, definition of groups and gestational age at sampling were most similar to the research by Bamberg et al [38] and Puchner et al [51], who found lower, but not significantly lower, levels of selected inflammatory mediators in women with spontaneous PTD, compared with women delivering at term.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies are conflicting, most likely due to dissimilarities in study design and diversities in study populations [26]. Some of the previous studies have reported higher levels of inflammatory biomarkers in mid-trimester amniotic fluid in women with a subsequent spontaneous PTD [21,23,37,[40][41][42][43][47][48][49][50]53,54,58], whereas other studies did not find any significant differences [25,26,38,39,[44][45][46]51,52,55,59]. Our study design, definition of groups and gestational age at sampling were most similar to the research by Bamberg et al [38] and Puchner et al [51], who found lower, but not significantly lower, levels of selected inflammatory mediators in women with spontaneous PTD, compared with women delivering at term.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different measurements and tests have been developed for the prediction of preterm labor [2]. The leading ones include cervical length measurement, fetal fibronectin testing, and biochemical markers obtained from maternal serum and amnion [4]. Maternal blood and amniotic fluid inflammatory markers may cause anxiety in pregnant women due to the interventional nature of the procedures.…”
Section: Introductionmentioning
confidence: 99%